(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current situation of sleep quality and identify some factors related to the sleep disturbances among young people in Vietnam in 2025. Subjects and methods: A cross-sectional descriptive study was conducted among 1,209 young individuals in Vietnam. Data were collected using an online questionnaire (Google Form), incorporating the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. A global PSQI score >5 was used to define sleep disturbance. Data were analyzed using R version 4.3.2. The Chi-square (χ²) test and logistic regression models were employed to identify associated factors, with a statistical significance level set at p<0.05 Results: The prevalence of poor sleep quality (sleep disturbance) among young people was 53.3%. The mean global PSQI score was 6.13±3.31. Sleep disturbance varied significantly across educational levels (p=0.001). The 15–18 age group had a higher prevalence of sleep disturbance than the 19–25 age group (61.0% vs. 52.3%; p=0.051) Conclusion: More than half of the young participants had poor sleep quality. The result highlight the need for public health interventions and educational programs to improve awareness and promote healthy sleep practices among young people in the current context.